2000
DOI: 10.1046/j.1464-410x.2000.00791.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of calcium phosphate‐associated proteins on calcium oxalate crystallization: α2‐HS‐glycoprotein, prothrombin‐F1 and osteopontin

Abstract: Objective To analyse urinary calcium phosphateassociated proteins and assess their inhibitory effects on calcium oxalate crystallization. Materials and methods Urine samples were collected over 24 h from ®ve healthy men and calcium phosphate crystallization induced with NaOH solution. The bound proteins were separated on a cellulose column. To examine the effect of urinary calcium phosphate-associated proteins on calcium oxalate crystallization, 60 L of urine was collected from the healthy men. The effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Clinical studies to date are inconclusive regarding the relationship between OPN and renal stone disease. Some investigators have reported decreased concentrations of OPN in urine from stone formers compared to normal individuals [123], while others have not [167]. A single-base mutation in the OPN gene is seen at significantly higher incidence in patients with recurrent stone formation or familial nephrolithiasis [168].…”
Section: Matrix Componentsmentioning
confidence: 99%
“…Clinical studies to date are inconclusive regarding the relationship between OPN and renal stone disease. Some investigators have reported decreased concentrations of OPN in urine from stone formers compared to normal individuals [123], while others have not [167]. A single-base mutation in the OPN gene is seen at significantly higher incidence in patients with recurrent stone formation or familial nephrolithiasis [168].…”
Section: Matrix Componentsmentioning
confidence: 99%
“…OPN is synthesized within the kidney and is present in human urine at levels that can effectively inhibit CaOx crystallization [21][22][23]. Indeed, reduced concentrations of OPN have been documented in urine from patients with renal stone disease compared with normal individuals [24,25]. In vitro data indicate that urinary OPN may inhibit the nucleation, growth, and aggregation of CaOx crystals in cultured renal epithelial cells [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic factors that regulate calcium metabolism and inflammation are possibly linked with nephrolithiasis. Genetic polymorphisms of CLDN14, CASR, OPN, ORAI1, and VDR were reported to be involved in calcium nephrolithiasis in humans [1923]. Our previous study indicated that genetic polymorphisms of ORAI1 are associated with susceptibility to calcium urolithiasis [6].…”
Section: Discussionmentioning
confidence: 99%